The Cure Rate of COVID-19 Patients with Comorbid Hypertension - Giri, Made Widiantara; I Made Subhawa Harsa (Nusantara Medical Science Journal, 2024)
Introduction: Coronavirus Disease 2019 (COVID-19) is an outbreak that has resulted in a global pandemic. In 2020, 185 countries were affected, and more than 3,000,000 cases have been reported worldwide, with more than 210,000 deaths. COVID-19 is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV 2), an RNA virus that can cause respiratory system disorders. Hypertension, commonly called high blood pressure, is a health problem that often occurs in the community because its prevalence is relatively high throughout the world. Approximately 7.5 million deaths, or 12.8% of all annual deaths in the world, are caused by hypertension. Generally, the presence of comorbid hypertension in COVID-19 can worsen the patient's condition. Methods:  This literature review study aims to determine the recovery rate of COVID-19 patients with comorbid hypertension. Journals in this literature review used three databases, including Google Scholar, PubMed, and Science Direct, using the keywords COVID-19 with Hypertension and COVID-19 with Hypertension. The literature search was adjusted based on the inclusion and exclusion criteria. Results: The search results obtained 25 journals consisting of 4 national journals and 21 international journals. The results showed that the average recovery rate for COVID-19 patients with comorbid hypertension was 75.40%. Factors influencing the recovery rate of COVID-19 patients with comorbid hypertension include ACE-2, ACEI/ARBs, age, male, and cytokines. Conclusions:  It can be concluded that the presence of comorbid hypertension affects the recovery rate of COVID-19 patients.